Flexible composite conductive textile and preparation method thereof

Through carbon nanotube surface modification and nanofiber spinning braiding technology, the problems of unstable conductivity and insufficient flexibility of traditional conductive textiles are solved, and textiles with high conductivity and good flexibility are prepared, which are suitable for a variety of applications. And maintain stable performance in extreme environments.

CN119287575APending Publication Date: 2025-01-10HUNAN INSTITUTE OF ENGINEERING
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411614751.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The problems of uneven distribution of conductive particles and degraded mechanical properties in traditional conductive textiles lead to unstable conductive properties and insufficient flexibility.

Method used

Through the integrated process of carbon nanotube surface modification and nanofiber spinning and braiding, uniform dispersion and firm adhesion of carbon nanotubes can be achieved, and textiles with high conductivity, excellent flexibility and comfort are prepared.

Benefits of technology

It achieves the improvement of the stability and flexibility of conductive properties, is suitable for many occasions where conductive properties are required, and maintains the conductive properties and structural stability in extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287575A_ABST
    Figure CN119287575A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of textile materials, in particular to a flexible composite conductive textile and a preparation method thereof.Carbon nanotubes are uniformly dispersed and firmly attached to the surfaces of fibers through surface modification of the carbon nanotubes in combination with a nanofiber spinning and weaving integrated process, so that the textile stable in conductivity and good in flexibility is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of textile materials, and in particular to a flexible composite conductive textile and a preparation method thereof. Background Art

[0002] With the advancement of science and technology and the increasing demand for the versatility of textiles, conductive textiles have shown broad application prospects in many fields, such as smart wearables, electromagnetic shielding, and antistatic. Carbon nanotubes (CNTs) have become an ideal material for the preparation of conductive textiles due to their unique electrical and mechanical properties. However, the dispersion of CNTs in the polymer matrix and the interfacial bonding force with the matrix are key factors affecting the performance of conductive textiles. Traditional preparation methods often have problems such as uneven dispersion of CNTs and poor conductivity.

[0003] Conventional conductive textiles are usually made by directly mixing conductive particles (such as conductive carbon, carbon black, etc.) into fibers or attaching them to the fiber surface through an adhesive. However, these methods have problems such as uneven distribution of conductive particles, unstable conductive properties, and decreased mechanical properties of the fibers. For example, the conductive fiber disclosed in Japanese Patent Laid-Open No. 11-350296 has insufficient conductive properties due to the uneven distribution of conductive particles in the fiber. Although the conductive resin molded body disclosed in Japanese Patent Laid-Open No. 2006-213839 uses carbon nanotubes as a conductive agent, the carbon nanotubes are not evenly attached to the fiber surface, resulting in the conductivity and mechanical properties of the molded body being affected.

[0004] In order to solve the above problems, the present invention proposes a new flexible composite conductive textile and a preparation method thereof. Through a specific carbon nanotube surface modification and nanofiber spinning and weaving integrated process, a textile with high conductivity, excellent flexibility and comfort is prepared, which is suitable for a variety of occasions requiring conductive properties. Summary of the invention

[0005] The purpose of the present invention is to provide a flexible composite conductive textile and a preparation method thereof. The method comprises surface modification of carbon nanotubes and an integrated process of nanofiber spinning and weaving to uniformly disperse the carbon nanotubes and firmly attach them to the fiber surface, thereby producing a textile with stable conductive properties and good flexibility.

[0006] In one aspect, the present invention provides a flexible composite conductive textile comprising nanofibers prepared from surface-modified carbon nanotubes.

[0007] Further, the carbon nanotubes include at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes. Preferably, the carbon nanotubes are single-walled carbon nanotubes.

[0008] Furthermore, the outer diameter of the carbon nanotube is about 2-20nm, and the length is about 5-50μm; preferably, the outer diameter of the carbon nanotube is about 5-30nm, and the length is about 5-15μm; more preferably, the outer diameter of the carbon nanotube is about 5-10nm, and the length is about 5-15μm.

[0009] Furthermore, the carbon nanotube surface modification step includes acid treatment and sensitization activation.

[0010] Furthermore, the acid solution is selected from one of sulfuric acid, nitric acid and hydrochloric acid.

[0011] Further, the acid solution concentration is 2-3 mol / L. Preferably, the acid solution concentration is 2.5 mol / L.

[0012] Further, the acid treatment reaction is stirred at a constant temperature of 60-90° C. for 3-5 hours. Preferably, the acid treatment reaction is stirred at a constant temperature of 65-85° C. for 3-5 hours. Preferably, the acid treatment reaction is stirred at a constant temperature of 80° C. for 4 hours.

[0013] Further, the sensitizing and activating agent is selected from one of PdCl2 (palladium chloride), TiCl2 (titanium dichloride), CrCl3 (chromium trichloride) and ThCl4 (thorium tetrachloride). Preferably, the sensitizing and activating agent is selected from PdCl2 (palladium chloride).

[0014] Further, the concentration of the sensitizing and activating agent is 0.05-0.20 mol / L. Preferably, the concentration of the sensitizing and activating agent is 0.08-0.18 mol / L. Preferably, the concentration of the sensitizing and activating agent is 0.1 mol / L.

[0015] Furthermore, the surface-modified carbon nanotubes, polyvinyl alcohol (PVA), and an appropriate amount of deionized water and / or a surfactant are mixed to prepare an electrospinning solution.

[0016] Furthermore, the surfactant is selected from one or more of sodium dodecyl sulfate (SDS), sodium alkylbenzene sulfonate (ABS), dodecyldimethylbenzyl ammonium chloride, dodecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, fatty acid sorbitan (Span), and polysorbate (Tween).

[0017] Further, the concentration of the surface-modified carbon nanotubes in the electrospinning solution is 0.1-0.5%. Preferably, the concentration of the surface-modified carbon nanotubes in the electrospinning solution is 0.2-0.4%. More preferably, the concentration of the surface-modified carbon nanotubes in the electrospinning solution is 0.3%.

[0018] Further, the mass ratio of the modified carbon nanotubes to polyvinyl alcohol is 1:100-5:100. Preferably, the mass ratio of the modified carbon nanotubes to polyvinyl alcohol is 2:100-4:100. More preferably, the mass ratio of the modified carbon nanotubes to polyvinyl alcohol is 3:100.

[0019] Further, the nanofiber is prepared by electrostatic spinning, wherein the spinning conditions are at room temperature, a spinning speed of 0.5-0.7 m / s, a spinning voltage of 15-20 kV, and a spinning distance of 10-30 cm. Preferably, the spinning conditions are at room temperature, a spinning speed of 0.6 m / s, a spinning voltage of 15-25 kV, and a spinning distance of 15-25 cm. More preferably, the spinning conditions are at room temperature, a spinning speed of 0.6 m / s, a spinning voltage of 18 kV, and a spinning distance of 20 cm.

[0020] Furthermore, the flexible composite conductive textile is woven with nanofibers, with a weaving density of 200 fibers / 10 cm, a weaving angle of 45°, and a warp and weft interlacing method for the fibers.

[0021] Furthermore, the resistivity of the flexible composite conductive textile is less than 1.0×10 ^3 Ω·cm, meeting the conductivity requirements.

[0022] Furthermore, the flexible composite conductive textile has no obvious damage after being bent at least 1000 times and has good flexibility.

[0023] Furthermore, the flexible composite conductive textile exhibits good comfort and no discomfort in a human wearing test.

[0024] Furthermore, the flexible composite conductive textile can maintain good conductive properties and structural stability in extreme environments such as high temperature (50°C), low temperature (-10°C), high humidity (90% RH) and low humidity (10% RH).

[0025] The flexible composite conductive textile and the preparation method thereof provided by the present invention exhibit the following significant technical effects:

[0026] 1. Excellent conductivity: Through the surface modified carbon nanotubes and nanofiber spinning and weaving process, the conductive performance of textiles is stable, and the resistivity is as low as 1.0×10 ^3 Ω·cm.

[0027] 2. Excellent flexibility: The textile can withstand multiple bends without damage, is flexible and durable, and is suitable for various application scenarios.

[0028] 3. Strong environmental adaptability: Under extreme temperature and humidity conditions, textiles maintain conductive properties and structural stability.

[0029] 4. Wide application: Applicable to multiple fields such as wearable devices and smart textiles, with broad market prospects

[0030] 5. Environmental protection and sustainability: Use environmentally friendly raw materials and processes to improve resource utilization and reduce waste.

[0031] 6. High human comfort: good trying-on experience, no discomfort, improving user experience.

[0032] In summary, the present invention has excellent performance in electrical conductivity, flexibility, environmental adaptability, application prospects, environmental protection and comfort, and has significant innovative value and practical value. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a picture of the product obtained in Example 1. DETAILED DESCRIPTION

[0034] The present invention is further described below in conjunction with specific embodiments.

[0035] The purity of carbon nanotubes is 98%.

[0036] Embodiment 1:

[0037] 1. Surface modification of carbon nanotubes:

[0038] First, 15g of multi-walled carbon nanotubes with an outer diameter of about 5-10nm and a length of about 5-15μm were dispersed in 400mL of a sulfuric acid solution with a concentration of 2.5mol / L, and stirred at 80°C for 4 hours to remove surface impurities and introduce more functional groups such as carboxyl groups. After the reaction, it was repeatedly washed with deionized water until neutral and vacuum dried at 80°C for 8 hours. Then, the modified carbon nanotubes were redispersed in 150mL of a palladium chloride (PdCl2) solution containing 0.1mol / L, stirred at room temperature for 2 hours, and further sensitized and activated. After the reaction, it was also washed with deionized water until neutral and vacuum dried at 80°C for 4 hours to obtain the final modified carbon nanotubes.

[0039] 2. Integration of nanofiber spinning and weaving:

[0040] Preparation of spinning solution: 1.5 g of the final modified carbon nanotubes was mixed with 50 g of polyvinyl alcohol (PVA), 443.5 mL of deionized water was added, and the mixture was stirred evenly at 50° C. to form a spinning solution.

[0041] Electrospinning: Inject the spinning solution into the liquid storage tank of the electrospinning equipment, adjust the spinning speed to 0.6m / s, the spinning voltage to 18kV, and the spinning distance to 20cm. Perform electrospinning at room temperature (about 25°C) and relative humidity of 45% to obtain nanofibers containing carbon nanotubes. In order to further improve the orientation and uniformity of the nanofibers, an auxiliary electric field or a collection device is used for directional collection.

[0042] Weaving process: The weaving density is 200 strands / 10cm, the weaving angle is 45°, and the fiber arrangement is warp and weft interlacing. During the weaving process, maintain room temperature (about 25°C) and relative humidity of 50%. Figure 1 shown.

[0043] 3. Performance test:

[0044] Conductivity test: At room temperature (about 25°C) and relative humidity of 50%, a four-probe tester was used to measure the conductivity of the textile. The measured resistivity of the textile was 1.0×10 ^3 Ω·cm, meeting the conductivity requirements.

[0045] Flexibility and comfort test: The flexibility of the textiles was tested using a bending fatigue tester at room temperature (about 25°C) and a relative humidity of 60%. After 1,000 bends, the textiles showed no obvious damage and good flexibility. At the same time, the comfort of the textiles was evaluated through human fitting tests, and the results showed that they were comfortable to wear without discomfort.

[0046] Durability test: The textile was placed in extreme environments such as high temperature (50°C), low temperature (-10°C), high humidity (90%RH) and low humidity (10%RH) for performance testing. The test results show that the textile can maintain good conductivity and structural stability in different environments.

[0047] Embodiment 2:

[0048] 1. Surface modification of carbon nanotubes:

[0049] First, 15g of single-walled carbon nanotubes with an outer diameter of about 5-10nm and a length of about 5-15μm were dispersed in 400mL of a sulfuric acid solution with a concentration of 2.5mol / L, and stirred at 80°C for 4 hours to remove surface impurities and introduce more functional groups such as carboxyl groups. After the reaction, it was repeatedly washed with deionized water until neutral and vacuum dried at 80°C for 8 hours. Then, the modified carbon nanotubes were redispersed in 150mL of a palladium chloride (PdCl2) solution containing 0.1mol / L, stirred at room temperature for 2 hours, and further sensitized and activated. After the reaction, it was also washed with deionized water until neutral and vacuum dried at 80°C for 4 hours to obtain the final modified carbon nanotubes.

[0050] 2. Integration of nanofiber spinning and weaving:

[0051] Preparation of spinning solution: 1.5 g of the final modified carbon nanotubes was mixed with 45 g of polyvinyl alcohol (PVA) powder, 443.5 mL of deionized water was added, and a magnetic stirrer was used to stir at 60° C. until the mixture was completely dissolved to form a uniform spinning solution.

[0052] Electrospinning: Inject the spinning solution into the liquid storage tank of the electrospinning equipment, adjust the spinning speed to 0.6m / s, the spinning voltage to 18kV, and the spinning distance to 20cm. Perform electrospinning at room temperature (about 25°C) and relative humidity of 45% to obtain nanofibers containing carbon nanotubes. In order to further improve the orientation and uniformity of the nanofibers, an auxiliary electric field or a collection device is used for directional collection.

[0053] Weaving process: the weaving density is 200 strands / 10cm, the weaving angle is 45°, and the fiber arrangement is warp and weft interlacing. The room temperature (about 25°C) and relative humidity of 50% are maintained during the weaving process.

[0054] 3. Performance test:

[0055] Conductivity test: At room temperature (about 25°C) and relative humidity of 50%, a four-probe tester was used to measure the conductivity of the textile. The measured resistivity of the textile was 8.0×10 ^2 Ω·cm, meeting the conductivity requirements.

[0056] Flexibility and comfort test: The flexibility of the textiles was tested using a bending fatigue tester at room temperature (about 25°C) and a relative humidity of 60%. After 1,000 bends, the textiles showed no obvious damage and good flexibility. At the same time, the comfort of the textiles was evaluated through human fitting tests, and the results showed that they were comfortable to wear without discomfort.

[0057] Durability test: The textile was placed in extreme environments such as high temperature (50°C), low temperature (-10°C), high humidity (90%RH) and low humidity (10%RH) for performance testing. The test results show that the textile can maintain good conductivity and structural stability in different environments.

[0058] Embodiment 3:

[0059] 1. Surface modification of carbon nanotubes:

[0060] First, 15g of single-walled carbon nanotubes with an outer diameter of about 5-10nm and a length of about 5-15μm were dispersed in 400mL of a sulfuric acid solution with a concentration of 2.5mol / L, and stirred at 80°C for 4 hours to remove surface impurities and introduce more functional groups such as carboxyl groups. After the reaction, it was repeatedly washed with deionized water until neutral and vacuum dried at 80°C for 8 hours. Then, the modified carbon nanotubes were redispersed in 150mL of a palladium chloride (PdCl2) solution containing 0.1mol / L, stirred at room temperature for 2 hours, and further sensitized and activated. After the reaction, it was also washed with deionized water until neutral and vacuum dried at 80°C for 4 hours to obtain the final modified carbon nanotubes.

[0061] 2. Integration of nanofiber spinning and weaving:

[0062] Preparation of spinning solution: 1.5 g of the final modified carbon nanotubes was mixed with 45 g of polyvinyl alcohol (PVA) powder, 443.5 mL of deionized water was added, and 0.5% of the total mass of the spinning solution was added with SDS, and stirred at 60°C using a magnetic stirrer until completely dissolved to form a uniform spinning solution.

[0063] Electrospinning: Inject the spinning solution into the liquid storage tank of the electrospinning equipment, adjust the spinning speed to 0.6m / s, the spinning voltage to 18kV, and the spinning distance to 20cm. Perform electrospinning at room temperature (about 25°C) and relative humidity of 45% to obtain nanofibers containing carbon nanotubes. In order to further improve the orientation and uniformity of the nanofibers, an auxiliary electric field or a collection device is used for directional collection.

[0064] Weaving process: the weaving density is 200 strands / 10cm, the weaving angle is 45°, and the fiber arrangement is warp and weft interlacing. The room temperature (about 25°C) and relative humidity of 50% are maintained during the weaving process.

[0065] 3. Performance test:

[0066] Conductivity test: At room temperature (about 25°C) and relative humidity of 50%, a four-probe tester was used to measure the conductivity of the textile. The measured resistivity of the textile was 5.0×10 ^2 Ω·cm, meeting the conductivity requirements.

[0067] Flexibility and comfort test: The flexibility of the textiles was tested using a bending fatigue tester at room temperature (about 25°C) and a relative humidity of 60%. After 1,500 bends, the textiles showed no obvious damage and good flexibility. At the same time, the comfort of the textiles was evaluated through human fitting tests, and the results showed that they were comfortable to wear without discomfort.

[0068] Durability test: The textile was placed in extreme environments such as high temperature (50°C), low temperature (-10°C), high humidity (90%RH) and low humidity (10%RH) for performance testing. The test results show that the textile can maintain good conductivity and structural stability in different environments.

[0069] Embodiment 4:

[0070] 1. Surface modification of carbon nanotubes:

[0071] First, 15g of single-walled carbon nanotubes with an outer diameter of about 5-10nm and a length of about 5-15μm were dispersed in 400mL of a sulfuric acid solution with a concentration of 2.5mol / L, and stirred at 80°C for 4 hours to remove surface impurities and introduce more functional groups such as carboxyl groups. After the reaction, it was repeatedly washed with deionized water until neutral and vacuum dried at 80°C for 8 hours. Then, the modified carbon nanotubes were redispersed in 150mL of a palladium chloride (PdCl2) solution containing 0.1mol / L, stirred at room temperature for 2 hours, and further sensitized and activated. After the reaction, it was also washed with deionized water until neutral and vacuum dried at 80°C for 4 hours to obtain the final modified carbon nanotubes.

[0072] 2. Integration of nanofiber spinning and weaving:

[0073] Preparation of spinning solution: 1.5 g of the final modified carbon nanotubes was mixed with 45 g of polyvinyl alcohol (PVA) powder, 443.5 mL of deionized water was added, and 0.8% of the total mass of the spinning solution was added with SDS, and stirred at 60°C using a magnetic stirrer until completely dissolved to form a uniform spinning solution.

[0074] Electrospinning: Inject the spinning solution into the liquid storage tank of the electrospinning equipment, adjust the spinning speed to 0.6m / s, the spinning voltage to 18kV, and the spinning distance to 20cm. Perform electrospinning at room temperature (about 25°C) and relative humidity of 45% to obtain nanofibers containing carbon nanotubes. In order to further improve the orientation and uniformity of the nanofibers, an auxiliary electric field or a collection device is used for directional collection.

[0075] Weaving process: the weaving density is 200 strands / 10cm, the weaving angle is 45°, and the fiber arrangement is warp and weft interlacing. The room temperature (about 25°C) and relative humidity of 50% are maintained during the weaving process.

[0076] 3. Performance test:

[0077] Conductivity test: At room temperature (about 25°C) and relative humidity of 50%, a four-probe tester was used to measure the conductivity of the textile. The measured resistivity of the textile was 4.5×10 ^2 Ω·cm, meeting the conductivity requirements.

[0078] Flexibility and comfort test: The flexibility of the textiles was tested using a bending fatigue tester at room temperature (about 25°C) and a relative humidity of 60%. After 1,500 bends, the textiles showed no obvious damage and good flexibility. At the same time, the comfort of the textiles was evaluated through human fitting tests, and the results showed that they were comfortable to wear without discomfort.

[0079] Durability test: The textile was placed in extreme environments such as high temperature (50°C), low temperature (-10°C), high humidity (90%RH) and low humidity (10%RH) for performance testing. The test results show that the textile can maintain good conductivity and structural stability in different environments.

[0080] Embodiment 5:

[0081] 1. Surface modification of carbon nanotubes:

[0082] First, 15g of single-walled carbon nanotubes with an outer diameter of about 5-10nm and a length of about 5-15μm were dispersed in 400mL of a sulfuric acid solution with a concentration of 2.5mol / L, and stirred at 80°C for 4 hours to remove surface impurities and introduce more functional groups such as carboxyl groups. After the reaction, it was repeatedly washed with deionized water until neutral and vacuum dried at 80°C for 8 hours. Then, the modified carbon nanotubes were redispersed in 150mL of a palladium chloride (PdCl2) solution containing 0.1mol / L, stirred at room temperature for 2 hours, and further sensitized and activated. After the reaction, it was also washed with deionized water until neutral and vacuum dried at 80°C for 4 hours to obtain the final modified carbon nanotubes.

[0083] 2. Integration of nanofiber spinning and weaving:

[0084] Preparation of spinning solution: 1.5 g of the final modified carbon nanotubes was mixed with 45 g of polyvinyl alcohol (PVA) powder, 443.5 mL of deionized water was added, and 1.0% of SDS by weight of the total spinning solution was added, and stirred at 60°C using a magnetic stirrer until completely dissolved to form a uniform spinning solution.

[0085] Electrospinning: Inject the spinning solution into the liquid storage tank of the electrospinning equipment, adjust the spinning speed to 0.6m / s, the spinning voltage to 18kV, and the spinning distance to 20cm. Perform electrospinning at room temperature (about 25°C) and relative humidity of 45% to obtain nanofibers containing carbon nanotubes. In order to further improve the orientation and uniformity of the nanofibers, an auxiliary electric field or a collection device is used for directional collection.

[0086] Weaving process: the weaving density is 200 strands / 10cm, the weaving angle is 45°, and the fiber arrangement is warp and weft interlacing. The room temperature (about 25°C) and relative humidity of 50% are maintained during the weaving process.

[0087] 3. Performance test:

[0088] Conductivity test: At room temperature (about 25°C) and relative humidity of 50%, a four-probe tester was used to measure the conductivity of the textile. The resistivity of the textile was measured to be 5.6×10 ^2 Ω·cm, meeting the conductivity requirements.

[0089] Flexibility and comfort test: The flexibility of the textiles was tested using a bending fatigue tester at room temperature (about 25°C) and a relative humidity of 60%. After 1,000 bends, the textiles showed no obvious damage and good flexibility. At the same time, the comfort of the textiles was evaluated through human fitting tests, and the results showed that they were comfortable to wear without discomfort.

[0090] Durability test: The textile was placed in extreme environments such as high temperature (50°C), low temperature (-10°C), high humidity (90%RH) and low humidity (10%RH) for performance testing. The test results show that the textile can maintain good conductivity and structural stability in different environments.

Claims

1. A flexible composite conductive textile, characterized in that: The invention relates to nanofibers prepared from surface-modified carbon nanotubes, wherein the carbon nanotubes are at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes.

2. The flexible composite conductive textile according to claim 1, characterized in that: The outer diameter of the carbon nanotube is about 2-20 nm, and the length is about 5-50 μm.

3. The flexible composite conductive textile according to claim 1 or 2, characterized in that: The carbon nanotube surface modification step includes acid treatment and sensitization activation; wherein the acid treatment uses a sulfuric acid, nitric acid or hydrochloric acid solution with a concentration of 2-3 mol / L, and reacts at a constant temperature of 60-90°C with stirring for 3-5 hours; the sensitization activation uses a PdCl2, TiCl2, CrCl3 or ThCl4 solution with a concentration of 0.05-0.20 mol / L.

4. The flexible composite conductive textile according to any one of claims 1 to 3, characterized in that: The nanofibers are prepared by an electrostatic spinning method, and the electrostatic spinning solution contains surface-modified carbon nanotubes, polyvinyl alcohol, and an appropriate amount of deionized water and / or a surfactant.

5. The flexible composite conductive textile according to claim 4, characterized in that: The mass ratio of the modified carbon nanotubes to polyvinyl alcohol is 1:100-5:

100.

6. The flexible composite conductive textile according to any one of claims 1 to 5, characterized in that: The spinning conditions of the nanofibers are as follows: at room temperature, a spinning speed of 0.5-0.7 m / s, a spinning voltage of 15-20 kV, and a spinning distance of 10-30 cm.

7. The flexible composite conductive textile according to any one of claims 1 to 6, characterized in that: The flexible composite conductive textile is woven with nanofibers, with a weaving density of 200 fibers / 10 cm, a weaving angle of 45°, and a fiber arrangement method of warp and weft interweaving.

8. The flexible composite conductive textile according to any one of claims 1 to 7, characterized in that: The resistivity of the flexible composite conductive textile is less than 1.0×10 ^3 Ω·cm.

9. The flexible composite conductive textile according to any one of claims 1 to 8, characterized in that: The flexible composite conductive textile has no obvious damage after being bent at least 1000 times.

10. A method for preparing the flexible composite conductive textile according to any one of claims 1 to 9, characterized in that: The method comprises the steps of surface modification of carbon nanotubes, preparation of electrostatic spinning solution, preparation of nanofibers by electrostatic spinning and nanofiber weaving.

Citation Information

Patent Citations

  • Woven fabric having excellent electrical conductivity and antistaticity and dustfree wear

    JP1999350296A

  • Conductive resin molded article

    JP2006213839A

  • Fibre structure of carbon nano tube / nano oxide nano composite material and preparation method and use thereof

    CN101139742A

  • Carbon nanotube / polyvinyl alcohol composite fibers and preparation method thereof

    CN103668528A

  • Carbon nanometer tube composite fibre with high orientation and production thereof

    CN1746343A